EFFECTS OF ACTIVITY-BASED STRATEGIES ON PRIMARY SCHOOL MATHEMATICS LESSON PLAN AND DELIVERY SKILLS AMONG PRE-SERVICE TEACHERS IN SOUTHWESTERN NIGERIA (2014)
Activity-based instructional strategies have been identified as being effective in the delivery of rule-governed subjects such as Mathematics. Two of these strategies are the Pupil-centred Activity-based Instructional Strategy (PAIS) and Teacher Demonstration Activity-based Strategy (TDAS). However, research findings have shown that a large number of primary school mathematics teachers trained in colleges of education in Nigeria have difficulty in developing lesson plans and delivering activity-based mathematics lessons. Past studies on activity-based strategies have focused on the general effectiveness of such strategies but have not sufficiently covered the skills of planning and delivery of lessons among the pre-service primary teachers. This study, therefore examined the effects of activity-based strategies on the primary mathematics lesson plan and delivery skills among pre-service teachers. The moderating effect of teachers’ numerical ability and gender were also examined. Pretest-posttest control group quasi-experimental research design was adopted for this study. The participants were 337 pre-service primary Mathematics teachers in three colleges of education in Southwestern Nigeria. Pupil-centred activity-based, teacher demonstration activity-based and conventional strategies were assigned to experimental-group I, experimental-group II and control group respectively. The study lasted 15 weeks for teaching and observation. Pre-Service Teachers Activity-Based Lesson Plan Scale (r = 0.84); Activity-Based Lesson Utilisation Scale (r = 0.79); Primary Numerical Ability Test (r = 0.83) and three instructional guides were the research instruments used. Eleven hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance, Analysis of Variance and Scheffe’s Post-hoc tests. There was a significant main effect of treatment on pre-service teachers’ lesson plan skills (F(2,318) = 628.15; p<0.05; partial η2 = .80). Pre-service teachers exposed to TDAS had a higher activity-based lesson plan score ( = 61.73) than those exposed to PAIS ( = 55.37) and those exposed to conventional strategy ( = 11.32). There were no significant main effects of numerical ability and gender on pre-service teachers’ lesson plan skills. There was significant difference between the treatment groups in primary Mathematics activity-based lesson delivery skills (F(2, 298) = 63.63; p<0.05; partial η2 = 0.30). Those exposed to PAIS had higher activity-based lesson delivery score ( = 59.4) than those exposed to TDAS ( = 49.7) and those exposed to conventional strategy ( = 46.2). There were no significant main effects of numerical ability and gender on pre-service teachers’ mathematics lesson delivery skills. Generally, these results imply that TDAS enhanced primary Mathematics activity-based lesson plan skills while PAIS enhanced the lesson delivery skills. Pupil-centred and teacher demonstration activity-based strategies enhanced pre-service primary mathematics teachers’ lesson plan and delivery skills more than the conventional strategy. Lecturers of primary school mathematics methodology courses in the colleges of education should be encouraged to acquire and utilise activity-based skills. Also, the contents of primary school mathematics methodology courses should include planning and delivery of the two strategies